102 Reduced Caloric Intake Increases the Incidence Rate of Gastric Ulcers in Growing Pigs. (12th April 2022) - Gabler, Nicholas K; Miller, Kayla A; De Mille, Carson M; Burrough, Eric R; Schweer, Wes P
Abstract: Our objective was to evaluate effects of a disease feed intake pattern on gastric ulcerations. Eighty mixed sex pigs (27.9 ± 1.45 kg BW) were allotted to individual pens and 2 treatments using a complete randomized design. All pigs were fed a 450 µm ground corn-soybean meal diet. Period 1 (d 0-28), all pigs were fed ad libitum. In period 2 (d 29-42), 40 pigs were fed daily based on their individual body weight (averaging 1.45x maintenance) to mimic a disease feed intake (RF) profile. The remaining pigs stayed on ad libitum feed (Ad). Pigs were weighed at d 0, 28 and 42, and feed disappearance measured to calculate ADG, ADFI and G:F within period. At d 42, all pigs were euthanized, stomach pH recorded, and stomach ulcerations scored (0-3 scale, with 0 being normal). Performance, pH and ulceration frequency data were analyzed with pig as the experimental unit and the fixed effect of feeding level. Performance was not different in period 1 ( P < 0.05). Compared with the Ad, RF pigs had lower ADG (1.10 vs 0.24 kg/d, P < 0.0001), ADFI (2.15 vs 0.85 kg/d, P < 0.0001) and G:F (0.51 vs 0.28, P < 0.0001) in period 2. Stomach pH was greater in the RF compared with the Ad pigs ( P < 0.001). A greater percentage of Ad pig stomachs scored normal to mild on pars oesophagea ulcerations (85 vs 62%), while a greater percentage of RF pigs had a maximum score compared with the Ad (38 vs 15%, respectively). RF pigs had a higher frequency of severe stomach body ulcerations (score 3) compared with the Ad (20.5 vs 15.0%, respectively). These data suggest that a disease feed intake pattern exacerbates the incidence of gastric ulcerations in grower pigs fed a fine micron ground corn.